Increasing Managerial Capabilities in Non-Profit Organizations in Leles Garut - Susanti, Illa; Susanti, Keuis Hera; Sihab, Alwi; Kusnadi, Sasqia Lisna Putri (Doctoral Program of Social Science, Pasundan University, 2023)
This community service activity aims to analyze strategies for increasing managerial capabilities in non-profit organizations in Leles Garut, Indonesia. Non-profit organizations are faced with unique challenges in their management and operations, requiring innovative approaches to increase effectiveness and social impact. The methods used in this activity include literature analysis, surveys of non-profit organizations in Leles Garut, and interviews with organizational leaders. The results of the activities show that technology integration, human resource development, and business strategy adaptation are key factors in improving managerial capabilities. Technology integration, such as the use of digital platforms for project management and data digitization, has been proven to increase operational efficiency. Training also plays an important role in updating the knowledge and managerial skills of staff. Human resource development through leadership training, mentoring programs, as well as regular evaluation and feedback, supports the formation of competent and adaptive teams. In addition, adapting business strategies through SWOT analysis strengthens an organization's capacity to face competition and changing needs. This activity concludes that non-profit organizations in Leles Garut can achieve improved performance and greater social impact by implementing managerial strategies tailored to their local needs and context. These results provide practical guidance for non-profit organizations in developing managerial capabilities, as well as a theoretical contribution to the non-profit organization management literature.